(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article presents the interim results of the ongoing research. At this stage, measurements are being made with a model in which two energy sources are already installed in the impeller with rotated wings. The main purpose of this research is to observe the impact of phase difference in the process of generating electricity and its efficiency by measuring the output power of a rectifier with voltage stabilizing circuits when changing the phase between the two generator sources. In the presence of two electrical energy sources, the voltage generated by these generator sources was measured, as well as the current when changing the phase (the mutual position of the coils relative to each other creates a phase difference in the generated current, and the magnets are connected to each other by a stationary mechanical connection). Methode - the phase change is measured when both sources have a common electrical connection and when both sources do not have a common electrical connection, at that moment they are connected only by the mechanical part. Research determines that when changing the angle between the coils, the phase between the voltage fluctuations generated by both sources’ changes. But the angles between the coils does not depend either on the variant of connecting the sources or on the connected load.